(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To analyze the selected factors associated with suicidal ideation among post-stroke patients at the National Geriatric Hospital. Methods: A cross-sectional descriptive study was conducted on 304 post-stroke inpatients from August 2025 to February 2026. Data were collected through direct clinical assessment and medical record review. Suicidal ideation was assessed through direct interviews, while mental health status and quality of life were evaluated using the PSQI, HADS, and SS-QOL-17 scales, respectively. Data were analyzed using SPSS version 27.0. Results: The prevalence of suicidal ideation was 11.8%. Male had a higher prevalence of suicidal ideation than female (OR crude = 2.85; p = 0.006). Younger patients, later post-stroke stage, and the presence of sequelae were significantly associated with suicidal ideation. Mental health factors, including insomnia, anxiety, depression, and poor quality of life, were strongly associated with suicidal ideation (p < 0.001). Conclusions: Suicidal ideation among post-stroke patients is associated with multiple factors, particularly mental health disorders and reduced quality of life. Early screening and timely intervention for these factors are essential for suicide prevention.